Anticancerous and Antioxidant Activity of Bioactive Compounds from Dunaliella Salina - Singh, Pritika (My University, 2014)
Dunaliella salina is a halotolerant, green microalga which is extensively studied for accumulation of carotenoids under stress conditions and has been consumed as food and natural medicine. Because of its high bioavailability of 9-cis form of β-carotene in dry biomass and omega-3 fatty acids, makes it a potent naturally derived antioxidant. The scope of this study was to investigate anticancer, antioxidant and antimicrobial properties of normal and stressed crude extract of Dunaliella salina. In the present work various stress parameters such as high salinity, high temperature and nitrogen stress to increase the agglomeration of bioactive compounds were studied. Results indicated that with increase in the stress levels pharmacological activity also increased. On these parameters total cell number, specific growth rate, carotenoid and protein content was analyzed. Non-stressed growth conditions were the optimum growth conditions for the maximum biomass .i.e., 1.7 M NaCl, 0.75 mM nitrogen concentration at 28⁰C, whereas 3.5 M NaCl concentration without nitrogen source at 37⁰C as were identified as optimum conditions for bioactive metabolites accumulation. Antioxidant activity in non-stressed Dunaliella was recorded as 14.96 % by DPPH assay, which significantly increased to 57.3 % under stress conditions. Similarly the cytotoxic effect of microalgae was studied on Human Breast Cancer cell MCF-7. MTT assay showed that 250 μg/ml of nitrogen stressed 0 M and 0.25 M Dunaliella cells considerably reduced MCF-7 cell proliferation by 53.7 % and 69.3 %, respectively. The salinity stressed at 3.0 M and 3.5 M NaCl Dunaliella extract (250 μg/ml), significantly reduced MCF-7 Cell proliferation by 33.42% and 47.87% respectively. Dunaliella salina has potent antibacterial and antifungal activity and these activities were significantly increased under stressed Dunaliella. Thus Dunaliella salina may be considered as a good candidate to be developed as a wholesome nutrient supplement and can be used to obtain antioxidant and cytotoxic agent.
MS, DBTS
Keywords: Dunaliella salina, MCF-7 cells, Antimicrobial activity, Antioxidants, β-carotene